A Review of Renewable Energy Development in PJM - Fan, Zhenyu (Journal of Technology Innovations in Renewable Energy, 2013)
As one of the world’s largest grid operators, PJM interconnection in the United State leads and promotes renewable energy and greener grid. The growth of solar, wind and other types are significant in recent years, as well as the continuing emergence of energy storage and energy efficiency technologies. All of this new growth is supported by adaptive market rules, stakeholder process, partnerships with industry groups and collaboration with members, state and federal agencies and commissions. With the emerging Smart Grid technologies, the U.S. electrical grid will evolve into a highly advanced, automated and interconnected network. Taking full advantage of renewable sources while dealing with the reliability challenges of the new resources will require a significant change in many aspects in power industry. The overview of the efforts to promote renovation and the ongoing and future renewable energy in PJM footprint is presented in this paper. The current state of art renewable energy development in operation and planning will also be discussed. Some renewable related projects such as on-going renewable integration studies, energy storage batteries and demand response will shed the light of the future trend.